8.5k views
4 votes
9. What’s the answer to this please

9. What’s the answer to this please-example-1
User Shaunee
by
5.4k points

1 Answer

1 vote

Answer:

W = 5

Explanation:

Simplify the brackets.

-2x^2 + wx - 4 - x^2 - 5x - 6 = -3x^2 - 10

Then simplify (-2x^2 + wx - 4 - x^2 - 5x - 6) to

( -3x^2 + wx - 10 - 5x)

This will give you 3x^2 + wx - 10 - 5x = -3x^2 - 10.

Now you need to cancel out -3x^2 on both sides.

wx - 10 - 5x = -10

Then cancel out -10 from both sides.

wx - 5x = 0

Now factor out the common term. (x)

w - 5 = 0.

giving you the answer w = 5.

welcome. *yeets*

User Stephen Holiday
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.